Structural style of the NW Zagros Mountains and the role of basement thrusting for its Mountain Front Flexure, Kurdistan Region of Iraq. (December 2020) - Zebari, Mjahid; Balling, Philipp; Grützner, Christoph; Navabpour, Payman; Witte, Jan; Ustaszewski, Kamil
Abstract: The NW segment of the Zagros Mountain Front Flexure in the Kurdistan Region of Iraq forms a prominent topographic and structural step separating the High Folded and Foothill zones. Due to scarcity of subsurface data, the geometry of faults underlying this flexure and the degree of basement involvement are poorly constrained. To overcome this, we estimated the structural relief along seven transects across the belt and reconstructed deformed geometries using balanced cross-sections. The average structural relief for six transects is around 2.6 km. Iterative kinematic forward modeling along one of these transects suggests that a multi-stage evolution involving both thin- and thick-skinned deformation can explain the observed structural relief. Our preferred model shows that early detachment folds in the Mesozoic to Neogene succession were overprinted by a NE-dipping basement-rooted thrust system with a cumulative displacement of 6.5 km. Up-dip, the basement thrust bifurcates into two splay thrusts. While the structurally higher splay accommodated 4.2 km of slip and amplified frontal anticlines to form the Mountain Front Flexure, the lower and younger splay took up 2.3 km of slip, which was mainly transferred into the Triassic basal detachment of the Foothill Zone. The shortening across the NW Zagros is calculated at c. 24.8 km. The shortening amount within the topographically low part of the belt implies that the Late Miocene to Quaternary shortening rate was much lower than the geodetically derived convergence rate. Highlights: The structural relief across the NW segment of the Zagros Mountain Front Flexure is 2.4–3 km. A balanced cross-section reveals 6.5 km reverse displacement on abasement thrust below the Mountain Front Flexure. The shortening along a regional cross-section is c. 24.8 km. The L. Miocene-Quaternary shortening rates in the belt were much lower than geodetically derived convergence rates.